Methodological diversity as an asset for transition-focused higher education research with students from refugee backgrounds - Baker, S.; Irwin, E.; Taiwo, M.; Singh, S.; Gower, Shelley; Dantas, Jaya (Johns Hopkins University Press, 2018)
This paper discusses the methodological and logistical complexities that underpin multimethod, multi-sited, multi-phased research with vulnerable communities. The project on which we draw was a 3-year Australian government-funded, longitudinal and cross-sectional exploration of students from refugee backgrounds (SfRBs) as they moved into, through and out of higher education from three different contexts, educational pathways and localities in Australia. While all students entering and participating in higher education may experience challenges, for SfRBs these are compounded by their linguistic and cultural diversity, instability, possible trauma and disrupted schooling. In the project presented in this article, these complexities and their relationships with transitions to higher education were captured through diverse methods and methodologies at three research sites, including longitudinal research with repeat interviews and cross-sectional, explorative methods. The opportunities provided by this methodological approach far outweighed the ethical and practical difficulties navigated by each of the research teams. The ‘thick’ data produced through prolonged and repeat engagements with a small cohort of participants at one site were made richer through explorations of differing social and geographical contexts across all three sites. Further, our collective interpretations of the data were made more robust through the reciprocity and reflexivity inherent in ethically researching with (not on) SfRBs and through multiple cross-site research team interactions. Introduction In order to make meaning of complex and dynamic phenomena like the transitions people make over time and space, a commensurately dynamic and flexible research design is required. In the case of educational transitions, the changes that students experience can include moving between educational levels (with their attendant practices, procedures, expectations and epistemologies), between geographic spaces, social networks, disciplines, modules and relationships. It is therefore important to develop rich pictures of how students experience their transitions because these changes in the student’s lives can significantly impact on their sense of self, on their